Addie D.

asked • 10/16/19# Sqrt{3+2sqrt(2)} to (-sqrt2) -1

Thank you so much for answering!

More

## 1 Expert Answer

Steven G. answered • 28d

College Math Professor

Let x = sqrt(3+2sqrt(2))

Then x^{2} = 3 + 2sqrt(2)

x^{2} - 3 = 2sqrt(2)

Now square both sides

x^{4} - 6x^{2} + 9 = 8

Solve .x^{4} - 6x^{2} + 1 = 0

Clearly, from the 1st line, x >0 so it is NOT correct that x = -sqrt(2) - 1 which is clearly negative.

## Still looking for help? Get the right answer, fast.

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

#### OR

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.

Mark M.

10/16/19